US-China strategic competition and ASEAN's regional challenges - Anderson, Lawrence (2023)
The regional security outlook in Asia is mixed. While COVID-19 appears to be under control, recovery is uneven and fragile. The risk of further pandemics, the climate crisis, food security problems, spiralling fuel costs and finance are just some of the transboundary challenges threatening the regional order. They will be with us for years to come. None can be resolved by any one country alone. The deteriorating relationship between China and the US will have a significant impact on the role ASEAN can play to promote regional stability and prosperity.